“To hell with the people in Preston”: The Inequalities of Integration at Graham Creighton High School, Cherry Brook, Nova Scotia, 1964-1979 - Slaunwhite, Stefanie R. (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2022)
Graham Creighton High School served as a pilot project for integration in the relatively isolated Eastern Shore area of the County of Halifax, Nova Scotia. The school, located in Cherry Brook, opened as an integrated institution in 1964 and served as the space where students from the surrounding Black and adjacent white communities were brought together to adhere to the local school board’s policy of integration. But while integration was the board’s policy, it was often not implemented in practice.